Smart home using PIR sensor (Based Indoor Location) - Jayiddin, Hairul; Ahmad, Anita; Abdul Rahim, Ruzairi; Ahmad, Nasarudin (Penerbit UTHM, 2016)
In smart homes, it is more energy-saving and comfortable if lighting, heating or home electronic devices could be control automatically according to people’s indoor position [1] and they should be controlled or monitored remotely using a television (TV) or personal digital assistant (PDA) [3]. Knowing human’s where about is also important to monitoring elderly people in their homes and helping them live a better life. [1]. Pyroelectric infrared (PIR) sensors are cheap, non-intrusive, very low power consumption and robust. Many existing approaches to human localization use the binary data output from PIR sensors [1]. PIR sensors are suitable to sense motion, because they are sensitive to the Infrared Radiation Changes (IRC) produced by human motion [2].